Drivers and Outcome of Motivation to Improve Work Through Learning: Evident from South East Asia - Ithnin, Nor Shamri; Ismail, Azman; Tharima, Ahmad Faiz; Ismail, Md Daud (UI Scholars Hub, 2022)
Research Aims: This study aims to examine the influence of social support on training transfer and investigate the mediating effect motivation to improve work through learning has on this relationship. Design/Methodology/Approach: This study used a quantitative design, utilising a cross-sectional survey via self-administered questionnaires, with experienced firefighters as respondents. Out of the 500 questionnaires received, 395 were valid responses and were further analysed using statistical analyses, such as confirmatory factor analysis and structural equation modelling. Research Findings: While peer support is a strong driver of training transfer, supervisor support has no significant influence on training transfer. Also, motivation to improve work through learning mediates the effect of social support on training transfer. Ample support from supervisors and peers to employees at work enhances employees’ motivation to improve work through learning and leads to applying the acquired knowledge, skills and abilities. Theoretical Contribution/Originality: This study provides evidence that human resource administrators should enhance the social support provided to employees to ensure that the new knowledge, skills and abilities acquired via training programmes are utilised on the job. Managerial Implications in the South East Asian Context: Social support is critical in public or private organisations. Adequate support to employees is needed to enable employees to benefit from the newly acquired knowledge, skills and attitudes gained through training. However, social support alone is insufficient without considering employees’ motivation to improve performance. Employees’ motivation to improve work through learning must be emphasised when promoting positive training transfer in organisations. Research Limitation & Implications: The cross-sectional approach and single informant limit the generalisability of the findings. Since the present study sample was drawn from one country and a single organisation, future studies could replicate the research in other countries and various organisation types to enrich the findings.